La littérature jeunesse pour contrer l’insécurité linguistique dans les écoles primaires québécoises - Jutras, Marie (Ponti/Ponts, 2021)
Linguistic insecurity is ever-present in Quebec and the school environment is particularly impacted by this phenomenon since it constitutes the core of formal language learning, but also because it represents a fundamental element in the identity-building of Quebecers. In elementary schools, children’s literature tends to replace or supplement certain learning traditionally done in textbooks and is emerging as a new didactic method for tackling various and sometimes delicate subjects. As the issues of linguistic variation and insecurity are closely linked to the identity construct, these matters can also be a challenge in terms of their integration in teaching practices. As language is considered the most important element when it comes to defining oneself as a culture and as a society, literature represents a key tool for introducing new linguistics lessons to children by inculcating both new knowledge and the notion of pleasure, an overriding aspect in the learning process. This article therefore aims to reflect on the potential usefulness of children’s literature in teaching basic linguistic notions at the start of schooling as well as to show how this relatively new teaching method can be part of the fight against linguistic insecurity in Quebec.